2015
DOI: 10.1128/jcm.03018-14
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of (1,3)-Beta- d -Glucan to Diagnosis of Invasive Candidiasis after Liver Transplantation

Abstract: bInvasive candidiasis (IC) causes high morbidity and mortality rates after liver transplantation, in part due to delayed diagnosis. The fungal cell wall component (1,3)-beta-D-glucan (BG) could be an early biomarker of IC. This preliminary prospective study was designed to evaluate the contribution of BG measurements to the diagnosis of IC after liver transplantation. All consecutive patients who underwent liver transplantation at Henri Mondor Hospital in France between January and June 2013 were enrolled pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
1
18
1
Order By: Relevance
“…Fungal colonization is often difficult to differentiate from true infection especially when the samples are positive for fungal elements from non‐sterile sites. Several studies have demonstrated the usefulness of serum biomarkers like Galactomannan index (GMI) and 1,3‐β D Glucan (BDG) as an adjunct for the diagnosis of IFI in general population, haematological malignancies and post–liver transplant recipients . However, their role has not been evaluated in patients with ACLF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fungal colonization is often difficult to differentiate from true infection especially when the samples are positive for fungal elements from non‐sterile sites. Several studies have demonstrated the usefulness of serum biomarkers like Galactomannan index (GMI) and 1,3‐β D Glucan (BDG) as an adjunct for the diagnosis of IFI in general population, haematological malignancies and post–liver transplant recipients . However, their role has not been evaluated in patients with ACLF.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the usefulness of serum biomarkers like Galactomannan index (GMI) and 1,3-β D Glucan (BDG) as an adjunct for the diagnosis of IFI in general population, 8 haematological malignancies 9 and post-liver transplant recipients. 10,11 However, their role has not been evaluated in patients with ACLF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This low incidence can be in part related to delayed or missed diagnoses owing to the lack of sensitivity and specificity of actual diagnostic tests. The early positivity and excellent sensibility of BG assay, which we observed in a previous study in a population of liver transplants , suggest that the detection of BG in the PF may help the diagnosis of PF yeast contamination and support the decision to promptly start pre‐emptive antifungal therapy. However, this test did not exist at the period of our study.…”
Section: Discussionmentioning
confidence: 53%
“…β‐D‐glucan is a cell wall polysaccharide present in fungi and primarily used for the diagnosis of invasive candidiasis, which is emerging as an important serological marker of candida infection . Various studies have used it primarily to diagnose invasive candidiasis in patients with leukemia and carcinomas, as well as in a post‐transplant setting . To our knowledge, none of the above mentioned studies have examined the role of serum β‐D‐glucan in diagnosing candidiasis in UC.…”
Section: Introductionmentioning
confidence: 99%